Indução de tetraplóides e alongamento de plantas de Dendrobium nobile Lindl. (Orchidaceae) - Vichiato, Mivia Rosa de Medeiros (2005)
The present study was developed at the campus of the Universidade Federal de Lavras, Minas Gerais, over period from January of 2003 to February of 2005, aiming at, for Dendrobium nobile Lindl., the induction and polyploidys identification, the stomatal analysis in diploid (2n=2x=38) and tetraploids (2n=4x=76) leaves, as well as the plant elongation with gibberellic acid application. In the first experiment, intact plants of D. nobile were completely submerged in 0,05% or 0,1% colchicine solution during 24, 48, 72 or 96 hours. For the polyploids plants identification by cytogenetics analysis, tips roots were pre-treatment in cold water for 24 hours, fixed in solution of acetic acid: chloroform: ethanol 95% (1:3:6) to 4o C for 24 hours and submitted to the conventional crushing technique The staining was done with solution of Giemsa 3% with phosphate buffer pH 6,8. In the second experiment, for the stomatal analysis in light microscopy, completely expanded leaves of the 3 o knot were fastened in FAA50, submitted to the usual procedures in vegetable and staining with safranine 1%. For the stomatal analysis in scanning electron microscopy, the leaves in the same conditions described for the light microscopy, were cut in 2 x 2 cm segments. The material was fixed in Karnovisk solution, pH 7.2 for 24 hours, pos-fixed with aqueous solution of tetroxid of osmio 1%, in cacodilato buffer 0,1 M, for 1 hour and dehydrated with growing series of acetone. Later, the material was dried until the critical point and, soon after, it was stuck to special blocks (“stubs") and covered with a metallic gold layer. In the third experiment, for the prolongation of plants of D. nobile with gibberellic acid application, intact plants with medium height of 4.74 cm received four pulverizations biweekly with four concentrations of GA3 (50, 100, 200 and 400 mg.L-1). It was concluded that the polyploidy induction in D. nobile, by immersion of the plants in colchicina solution is viable, obtaining larger number of individuals polyploidys (29,17%) in the 0,1% concentration by 96 hours. The D. nobile plants presented elliptic stomata with lateral gradually tilted, being the stomatal size inversely proportional at the ploidy level. The polyploidys plants presented smaller growth when compared with the diploid ones. The acid giberélico in the concentrations from 50 to 400 mg.L-1 is equally efficient in the prolongation of plants.